Analisis Perbedaan Tahapan Berpikir Geometri Ditinjau dari Pemahaman Konsep Geometri dan Evaluasi Formatif pada siswa SMP - Zamzaili Zamzaili; Baki Swita; Saleh Haji (Absis: Mathematics Education Journal, 2023)
The purpose of this study was to determine the effect of different stages of geometric thinking in terms of understanding the concept of geometry and formative evaluation. The sampling technique used in this study was simple random sampling, so that a sample of 90 students. The research instrument is a test of the ability to understand geometric concepts, a geometric thinking level test and formative evaluation. The panelist test was carried out using the Aiken and Hoyt formula to determine the validity and consistency of the instrument, while the test was to determine the difficulty index, discriminating power, validity and reliability of the instrument. The data analysis technique used discriminant analysis. The results showed that (1) understanding of geometric concepts significantly affected the differences in students' geometric thinking level achievement, (2) formative evaluation significantly influenced students' geometric thinking level achievement differences, (3) discriminant function equation D = -11.743 + 0.0034X1 + 0.125 X2 to predict the achievement of geometric thinking level, (4) The percentage accuracy of the discriminant function equation in predicting the difference in the achievement of students' thinking level is 98.9%.